Coccidiosis as A Predisposition Factor for Necrotic Enteritis in Poultry and Their Prevention - Ening Wiedosari; Y Sani (Indonesian Center for Animal Research and Development, 2020)
Coccidiosis and necrotic enteritis are both affecting the digestive tract of chicken and both are major enteric disease that mainly affect poultry. Among the enteric diseases, necrotic enteritis is a major problem. Coccidiosis is caused by the protozoan of Eimeria sp, and is commonly found as a predisposition factor for necrotic enteritis caused by Clostridum perfringens. Both diseases are commonly shown similar pathological change namely necrosis of epthelial cells in the intestinal mucosa. The diseases have great economic impact in poultry productions, due to the increased mortality, decreased performance and medication costs. Control of these diseases are commonly treated with antibiotics and ionophores. However, an intensive use of these drugs in feed may cause the emergence of drug-resistance against some strains of Eimeria sp.and Cl. Perfringens and an increased chance of contamination in animal products for human consumption. The paper is discussing the occurrence of necrotic enteritis especially due to the coccidian as a major predisposition factor and the development of alternative control strategies for avian coccidiosis and necrotic enteritis, by modulating intestinal health.